The Cytochrome P450 Monooxygenase Inventory of Grapevine (Vitis vinifera L.): Genome-Wide Identification, Evolutionary Characterization and Expression Analysis - Jiu, Songtao; Xu, Yan; Wang, Jiyuan; Wang, Lei; Liu, Xunju; Sun, Wanxia; Sabir, Irfan ali; Ma, Chao; Xu, Wenping; Wang, Shiping; Abdullah, Muhammad; Zhang, Caixi (Frontiers in Genetics, 2020)
The cytochrome P450 (CYP) monooxygenases superfamily, belonging to heme-thiolate protein products, play a vital role in metabolizing physiologically valuable compounds in plants. To date, CYP superfamily genes have not yet been characterized in grapevine (V. vinifera L.), and their functions remain unclear. In this study, a sum of 236 VvCYPs, divided into 46 families and clustered into nine clans, have been identified based on bioinformatics analyses in grapevine genome. The characteristics of both exon-intron organizations and motif structures further supported the close evolutionary relationships of VvCYPs subfamily as well as the reliability of phylogenetic analysis. The gene number-based hierarchical cluster of CYP subfamilies of different plants demonstrated that the loss of CYP families seems to be limited to single species or single taxa. Promoter analysis elucidated various cis-regulatory elements related to phytohormone signaling, plant growth and development, as well as abiotic/ biotic stress responses. The tandem duplication mainly contributed to the expansion of VvCYPs subfamily, followed by singleton duplication in grapevine. Global RNA-sequencing data of grapevine showed functional divergence of VvCYPs as diverse expression patterns of VvCYPs in various organs, tissues and developmental phases, which were confirmed by quantitative real-time reverse transcription PCR (qRT-PCR). Taken together, our results provided valuable inventory for understanding the classification and biological functions of the VvCYPs and paved the way for further functional verification of these VvCYPs, and is helpful to grapevine molecular breeding.